Can information about "safe places" reduce female victimisation in Honduras? a quasi-experimental evaluation of the safeWalking app. Issue 4 (2nd October 2022) - Capellan, Joel; Kim, Chunrye; Porter, Jeremy; Sung, Hung-En
ABSTRACT: SafeWalking is of a prevention tool that identifies safe areas for women in public spaces in the City of Santa Rosa de Copan, Honduras. The current study examines the effect of using this phone app on users' self-rated information about "safe places, " the number of precautionary behaviours, and victimisation. This study also examines its effect on constructs, such as fear of crime, perceived safety, and risk of victimisation. Using a pre-test and post-test design, we find that those assigned in the treatment group (i.e., the app users) experienced a significant increase in self-reported knowledge of the dangerous areas in Santa Rosa de Copan. Despite increased knowledge, there was no statistically significant effect on the number of precautionary behaviours and odds of victimisation of the app users. We discuss lessons learned, implications, and ways to improve future iterations of this and similar crime prevention applications.